The im/mobilities of women: Abortion travel from Texas to other states in the U.S. - Paruzel, Natalie (Université d'Ottawa | University of Ottawa, 2024)
Following the implementation of Senate Bill 8 (SB 8) on 1 September 2021 in Texas, a restrictive abortion law that banned all abortions after six weeks of gestation except to save the pregnant woman’s life, women seeking abortions looked to travel out of state to access abortion services. Using an abortion im/mobility theoretical framework and a feminist critical discourse analysis (CDA), this Major Research Project (MRP) demonstrates the negative impacts of SB 8 on women’s access to abortion services and their travel or lack of travel in the six months following its implementation. A feminist CDA was conducted on 23 articles published by The Texas Tribune during this period. SB 8 had a negative impact on women in Texas, abortion providers inside and outside Texas, pro-choice organizations, and more. In the first three months after the implementation of SB 8, some women in Texas were able to travel out of state, while others could not. Between the fourth and sixth months after the implementation of SB 8, the adverse effects of SB 8 were being felt by women and abortion providers outside Texas. This MRP demonstrates how SB 8 had a negative impact on women’s abortion im/mobilities.